Feeding behavior of Morpho butterflies (Lepidoptera: Nymphalidae: Morphinae) in a seasonal tropical environment - Young, Allen M. (Revista de Biología Tropical, 1975)
Observations in a semi-deciduous tropical wet forest in Guanacaste, Costa Rica, early in the dry season (December 1973 ) revealed that adults of the butterfly Morpho peleides (Lepidoptera: Nymphalidae: Morphinae) feed on tiny sap flows on exposed roots of the tree Samanea saman (Leguminoseae). These observations supplement earlier studies on the association of the butterflies with fallen, decaying fruits of the tree Guazuma ulmifolia (Sterculiaceae) in the same forest but during the previous dry season (January 1973). Morphoes collect in small groups of both sexes on the tree sap flows along with several species of ants. These feeding clubs, which are formed daily, usually in the afternoons, are tightly structured in that adults feed very closely together with no indications of agonistic behavior or courtship. When suddenly disturbed, the butterflies cease feeding and fly around the area before settling on nearby vegetation. The feeding behavior is different when morphoes feed on juices of Guazuma fruits: adults are widely dispersed and no feeding clubs are formed. Guazuma trees are more abundant in this forest and scattered over a larger area than the few Samanea trees. The association of Pierella luna; with the tree sap flows and the conspicuous lack of Caligo memmon, both abundant butterflies, is discussed from the standpoint of phylogenetic relationship between the Satyrinae and Morphinae. The implications of the changeover in feeding behavior of Morpho are discussed in terms of seasonality and destruction of forests by agricultural practices. Experiments employing baits predict changes in the dispersion of the adult population at different times during the dry season.